1. The problem statement, all variables and given/known data Prove that a.) (1-(1/n2))n > 1- 1/n b.) (1+ 1/(n-1))n-1 < (1 + 1/n)n when n=2,3,4,5,... 2. Relevant equations Bernoulli's inequality (1+x)n ≥ 1+nx, when x ≥-1 and n=2,3,4,5,... (1+x)n >1+nx, when x ≥-1, x≠0 and n=2,3,4,5,.. 3. The attempt at a solution a.) I applied Bernoulli's inequality. First I checked 'the requirements'. -1/n2 > -1 because n=1,2,3,... and -1/n2 ≠ 0 OK Then (1-(1/n2))n > 1+ (- 1/n2)*n=1- 1/n Ok, done. b.) I think I am supposed to apply Bernoulli's inequality as in part a, but don't have an idea how to get started.